Freirean pedagogy, praxis, and possibilities : projects for the new millennium - Steiner, Stanley F. (Garland reference library of social science, 2000)
This volume is a testament to the works of Paulo Freire in the field of education as well as the life of the man. Important new dimensions to the revolutionary, innovative ideas that Freire bequeathed are explored.